Does chlorhexidine improve periodontal health and bacterial profiles in patients with special health care needs? A systematic review and meta-analysis - Sharma, Deepak; Liu, Han-Pang; Hsu, Yung-Ting; Sheyda, Fatima; Forsyth, Anna; Nelson, Travis (Frontiers in Oral Health, 2025)
ObjectivesThe purpose of this systematic review was to evaluate the effectiveness of chlorhexidine (CHX)-containing products as adjuncts to mechanical oral hygiene practices in maintaining gingival health in patients with intellectual disability.Materials and methodsAn electronic search was conducted in three databases—PubMed, Embase, and Web of Science—1945- December 31, 2024. Two calibrated independent reviewers assessed the selected studies based on the inclusion and exclusion criteria. The main outcomes measured were changes in the gingival index, plaque index, and complications. A meta-analysis was performed to analyze the efficiency of adjunct CHX products compared with controls (mechanical plaque removal only). Additionally, meta-regression was conducted to investigate the factors contributing to these outcomes.ResultsTwelve randomized controlled trials involving individuals with special health care needs (SHCN) were included across varied clinical settings. CHX use was associated with a statistically significant reduction in plaque accumulation (Hedges' g = −1.491; 95% CI: −2.067 to −0.914; P < .001; I2 = 37.3%), with the greatest reductions observed in studies using spray and gel delivery methods. Gingival inflammation also decreased significantly across studies (mean difference = −0.214; 95% CI: −0.306 to −0.121; P < .001), with 0.2% CHX formulations demonstrating the most consistent improvement.ConclusionIn patients with SHCN short–term use (4–6 weeks), especially with 0.2% formulations, appeared to offer the greatest benefit while maintaining acceptable tolerability. While adverse effects such as tooth staining and taste alterations are common, they are generally mild and self-limiting. These findings support the short-term use of CHX as an adjunctive measure in oral hygiene management for individuals with SHCN, with use tailored to the patient's needs and monitored closely by a dental provider to minimize complications.Systematic Review Registration(CRD420251003198).